2021
DOI: 10.32744/pse.2021.5.28
|View full text |Cite
|
Sign up to set email alerts
|

The effect of airline service major students’ employment stress on learned helplessness and employment preparation behavior: a moderated mediation model of resilience

Abstract: Introduction. Employment stress among airline service major students is very high, because airlines have not been recruiting during the COVID-19 pandemic, which has led to high learned helplessness and less employment preparation behavior among students. Thus, the purpose of this study was to verify the effect of resilience, one of the positive psychological variables that decrease the negative mutual influence between learned helplessness and employment preparation behavior. Samples and methods. The particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…Following data collection, this study conducted frequency analysis for demographic information. The ratio of female to male students was 90% to 10%, respectively, which is similar to the actual proportions of female and male flight attendants in South Korea [34].…”
Section: Data Collection and Samplessupporting
confidence: 76%
See 1 more Smart Citation
“…Following data collection, this study conducted frequency analysis for demographic information. The ratio of female to male students was 90% to 10%, respectively, which is similar to the actual proportions of female and male flight attendants in South Korea [34].…”
Section: Data Collection and Samplessupporting
confidence: 76%
“…The measurement of employment stress perceived by airline service major students was developed by Park & Jeon [34]. The measurement items of employment stress consist of 'employment anxiety, 'employment worry', and 'employment fear'.…”
Section: Employment Stressmentioning
confidence: 99%
“…Following data collection, this study conducted the frequency analysis for demographic information. The ratio of female to male students was 88.2% to 11.8%, respectively, which is similar to the actual proportion of female and male flight attendants in South Korea [13]. The respondents among airline service major students consisted of sophomores (40.1%), juniors (30.9%), and seniors (29%) in South Korean universities.…”
Section: Data Collection and Samplessupporting
confidence: 67%
“…Studies have proven that resilience moderated between-student-related variables. In a study [13] examining airline service major students' learned helplessness during the COVID-19 pandemic, such learned helplessness was shown to decrease students' employment preparation behavior, and resilience was found to reduce the negative impact between learned helplessness and employment preparation behavior. Bang et al [20] found that tourism-related major students' employment stress was negatively associated with adaptation to college life, and that resilience played a moderating role in preventing students with employment stress from not maladapting to college life.…”
Section: Moderating Effect Of Resiliencementioning
confidence: 99%
See 1 more Smart Citation